Transient analysis of an FHR coupled to a helium Brayton power cycle. (August 2015) - Chen, Minghui; Kim, In Hun; Sun, Xiaodong; Christensen, Richard; Utgikar, Vivek; Sabharwall, Piyush
Abstract: The Fluoride salt-cooled High-temperature Reactor (FHR) features a passive decay heat removal system and a high-efficiency Brayton cycle for electricity generation. It typically employs an intermediate loop, consisting of an intermediate heat exchanger (IHX) and a secondary heat exchanger (SHX), to couple the primary system with the power conversion unit (PCU). In this study, a preliminary dynamic system model is developed to simulate transient characteristics of a prototypic 20-MWth Fluoride salt-cooled High-temperature Test Reactor (FHTR). The model consists of a series of differential conservation equations that are numerically solved using the MATLAB platform. For the reactor, a point neutron kinetics model is adopted. For the IHX and SHX, a fluted tube heat exchanger and an offset strip-fin heat exchanger are selected, respectively. Detailed geometric parameters of each component in the FHTR are determined based on the FHTR nominal steady-state operating conditions. Three initiating events are simulated in this study, including a positive reactivity insertion, a step increase in the mass flow rate of the PCU helium flow, and a step increase in the PCU helium inlet temperature to the SHX. The simulation results show that the reactor has inherent safety features for those three simulated scenarios. It is observed that the increase in the temperatures of the fuel pebbles and primary coolant is mitigated by the decrease in the reactor power due to negative temperature feedbacks. The results also indicate that the intermediate loop with the two heat exchangers plays a significant role in the transient progression of the integral reactor system. Highlights: A preliminary dynamic system model is developed to simulate transient characteristics of an FHR. Designs of an IHX and an SHX are developed for the FHTR. Three transient scenarios are investigated, i.e., reactivity insertion, helium flow rate step increase, and helium temperature step increase. The intermediate loop plays a significant role in the transient progression.